2017
DOI: 10.1108/el-06-2016-0140
|View full text |Cite
|
Sign up to set email alerts
|

The use of electronic resources by undergraduate students at the University of Venda, South Africa

Abstract: Purpose This paper aims to establish the level of use of the electronic resources at the University of Venda, which is one of the previously disadvantaged universities in South Africa. It identifies the different electronic resources used at the university, determines the level of awareness and training in the use of these resources and suggests ways in which electronic resources may be enhanced. The rapid changes in the information and communication technology (ICTs) have influenced service delivery in academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…Academic libraries all over the world are experiencing a paradigm shift in acquiring, storing and retrieving information, because of the application of information communication technologies (ICTs). Libraries organised with ICTs can offer friendlier information retrieval services to users [15,20,21]. In the current technology-rich educational environment, most of the information is stored and retrieved with the help of online databases.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Academic libraries all over the world are experiencing a paradigm shift in acquiring, storing and retrieving information, because of the application of information communication technologies (ICTs). Libraries organised with ICTs can offer friendlier information retrieval services to users [15,20,21]. In the current technology-rich educational environment, most of the information is stored and retrieved with the help of online databases.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In terms of creating awareness of digital libraries in distance education, it is suggested that intensive education campaigns be embarked upon to, first and foremost, change the negative perception and attitude of distance education stakeholders on the value of digital library resources in their teaching and learning activities as negative attitudes are known to negatively affect the use of digital resources in libraries (Tlakula & Fombad, 2017). This campaign cannot succeed without a plan (Owusu-Ansah et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(Okoroma, 2018), also reporting from the University of Ibadan in Nigeria, underscored the importance of awareness in the use of digital library resources, pointing out that lecturers at the University were not familiar with the institutional repository of the University including its aims and potential benefits. From the University of Venda in South Africa, (Tlakula & Fombad, 2017) found undergraduate students' awareness of electronic library resources to be low. The implication was that the students misunderstood electronic resources to be web-based resources.…”
Section: Related Literaturementioning
confidence: 99%
“…As the utilization of electronic assets is as yet a state of conversation for some researchers, they have concentrated on the benefits and impediments of these assets and how the understudies utilize these assets. Singh2013, Dattatraya andet al 2013, Tlakula andFombad (2017) (Akuffo & Budu 2019, Mehla 2018, Sharma. 2019, Toyo 2017.…”
Section: Review Of the Related Studiesmentioning
confidence: 99%